Complete sequencing of ape genomes - DongAhn Yoo; Arang Rhie; Prajna Hebbar; Francesca Antonacci; Glennis A. Logsdon; Steven J. Solar; Dmitry Antipov; Brandon D. Pickett; Yana Safonova; Francesco Montinaro; Yanting Luo; Joanna Malukiewicz; et al. (Nature, 2025)
Abstract The most dynamic and repetitive regions of great ape genomes have traditionally been excluded from comparative studies 1–3 . Consequently, our understanding of the evolution of our species is incomplete. Here we present haplotype-resolved reference genomes and comparative analyses of six ape species: chimpanzee, bonobo, gorilla, Bornean orangutan, Sumatran orangutan and siamang. We achieve chromosome-level contiguity with substantial sequence accuracy (<1 error in 2.7 megabases) and completely sequence 215 gapless chromosomes telomere-to-telomere. We resolve challenging regions, such as the major histocompatibility complex and immunoglobulin loci, to provide in-depth evolutionary insights. Comparative analyses enabled investigations of the evolution and diversity of regions previously uncharacterized or incompletely studied without bias from mapping to the human reference genome. Such regions include newly minted gene families in lineage-specific segmental duplications, centromeric DNA, acrocentric chromosomes and subterminal heterochromatin. This resource serves as a comprehensive baseline for future evolutionary studies of humans and our closest living ape relatives.